Chemoreactome analysis of 7-hydroxymatairesinol, 17-estradiol, phytoestrogen β-sitosterol and epigallocatechin-3-gallate - I. Yu. Torshin; A. N. Rubashkina; N. P. Lapochkina; O. A. Gromova (IRBIS LLC, 2020)
The results of the evaluation of 7-hydroximatairesinol (7-HMR) properties in comparison with control molecules (17-estradiol, phytoestrogen β-sytostirol, epigallocatechin-3-gallate) are presented. The results of chemoreactomic modeling allowed to formulate the molecular mechanisms of 7-HMR pharmacological effects for anti-inflammatory (inhibition of 5-lipoxygenase, matrix metalloproteinase MMR2, mitogen-activated kinase p38-alpha, leukotriene-b4 receptor, prostacyclin receptor), antitumor (antioxidant effect due to inhibition of hemoxygenase-2, inhibition of cyclin dependent kinases 3 and 4, epidermis growth factor, protein mTOR), vasodilator (inhibition of adrenoreceptors and renin), antibacterial and antiviral (inhibition of viral proteases 3C) properties of 7-HMR molecule.